Counterfactual coercion: Could harsher sanctions against Russia have prevented the worst? - Thies Niemeier; Gerald Schneider (Research & Politics)
Numerous studies show that properly designed economic sanctions can force the target to refrain from violating international norms. However, policymakers cannot integrate this finding into their ex ante assessments of whether more forceful coercive measures could prevent military coups, human rights violations, or a war of aggression such as the Russian invasion of Ukraine. In this article, we address this shortcoming and introduce counterfactual predictions to answer the what-if question of whether adequate sanctions by the European Union and the United States could have provoked targets to abandon severe norm violations. To this end, a training data set from 1989 to 2008 is used to predict the success of sanctions from 2009 to 2015. Our policy counterfactuals for key sanction cases suggest that stricter EU coercion against Russia after the annexation of Crimea could have triggered policy concessions from the regime of President Putin.